Models Hosts for the Study of Oral Candidiasis - Junqueira, Juliana Campos [UNESP] (Springer-verlag Berlin, 2012)
Oral candidiasis is an opportunistic infection caused by yeast of the Candida genus, primarily Candida albicans. It is generally associated with predisposing factors such as the use of immunosuppressive agents, antibiotics, prostheses, and xerostomia. The development of research in animal models is extremely important for understanding the nature of the fungal pathogenicity, host interactions, and treatment of oral mucosa! Candida infections. Many oral candidiasis models in rats and mice have been developed with antibiotic administration, induction of xerostomia, treatment with immunosuppressive agents, or the use of germ-free animals, and all these models has both benefits and limitations. Over the past decade, invertebrate model hosts, including Galleria mellonella, Caenorhanditis elegans, and Drosophila melanogaster, have been used for the study of Candida pathogenesis. These invertebrate systems offer a number of advantages over mammalian vertebrate models, predominantly because they allow the study of strain collections without the ethical considerations associated with studies in mammals. Thus, the invertebrate models may be useful to understanding of pathogenicity of Candida isolates from the oral cavity, interactions of oral microorganisms, and study of new antifungal compounds for oral candidiasis.